2021
DOI: 10.1039/d1ra01607e
|View full text |Cite
|
Sign up to set email alerts
|

A hydrothermal synthesis of Ru-doped LiMn1.5Ni0.5O4 cathode materials for enhanced electrochemical performance

Abstract: An Ru-doped spinel-structured LiNi0.5Mn1.5O4 (LNMO) cathode has been prepared via a simple hydrothermal synthesis method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
(57 reference statements)
0
5
0
1
Order By: Relevance
“…Figure b displays the Mn 2p spectra, and one can observe the appearance of two peaks located at 642.18 and 653.53 eV, which corresponds to Mn 3/2 and Mn 1/2 , respectively; the asymmetry of the two peaks indicates the existence of the mixed valent Mn ions . The peak fitting of the signal at 642 eV showed that Mn 3/2 could be resolved into two peaks at 641 and 643 eV, which can be attributed to Mn 3+ and Mn 4+ , respectively. , …”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Figure b displays the Mn 2p spectra, and one can observe the appearance of two peaks located at 642.18 and 653.53 eV, which corresponds to Mn 3/2 and Mn 1/2 , respectively; the asymmetry of the two peaks indicates the existence of the mixed valent Mn ions . The peak fitting of the signal at 642 eV showed that Mn 3/2 could be resolved into two peaks at 641 and 643 eV, which can be attributed to Mn 3+ and Mn 4+ , respectively. , …”
Section: Resultsmentioning
confidence: 93%
“…43 The peak fitting of the signal at 642 eV showed that Mn 3/2 could be resolved into two peaks at 641 and 643 eV, which can be attributed to Mn 3+ and Mn 4+ , respectively. 44,45 3.4. Oxygen Stoichiometry and Elemental and Microstructural Analyses.…”
Section: X-ray Photoelectron Spectroscopy (Xps) Analysismentioning
confidence: 99%
“…水/溶剂热法利用体系在高温下的自生压力实 现晶粒生长, 其优势在于所制备的晶粒发育相对完 整、粒径尺寸较小且分布均匀 [39][40][41][42] 。Yue 等 [43] 利用 水热法合成了 LiTi 2 (PO 4 ) 3 , 他们将 Li 2 O、TiO 2 和 P 2 O 5 置于反应釜中, 250 ℃保温 5~7 d 制备了立方形 态的目标产物, 其粒径在 40~60 μm。Liang 等 [44] 图 3 LiTi 2 (PO 4 ) 3 纳米线(LTPNMs)的制备过程示意图 [38] Fig. 3 Schematical illustration of the fabrication process of lithium titanium phosphate nanowires (LTPNMs) [38] 以 LiOH、 H 3 PO 4 和钛粉为原料, 钽片为基板, 在 220 ℃ 恒温 24 h 获得了薄膜电极材料。但 Yue 等和 Liang 等均未对产物进行深入的电化学性能研究。Li 等 [45] 采用水热法, 以…”
Section: 水/溶剂热法unclassified
“…In addition, the inclusion of suitable metal dopants were able to eliminate the impurity phases. Facile hydrothermal method suggested by Zhang et al achieved a highest initial discharge capacity (352.8 mAhg −1 ) with layered material and faded drastically after 50 cycles with a capacity retention of 75.5% 8‐11 …”
Section: Introductionmentioning
confidence: 99%